(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This paper examines how English-language news framing is pragmatically recast for Russian and Uzbek readers. Using three Reuters items in technology, finance, and climate reporting, it compares the headline and lead sentence with Russian and Uzbek renderings prepared for controlled analysis. The comparison tracks agency, compressed terminology, evaluative tone, and information density. Across the sample, Russian tends to preserve more of the compact analytical code typical of English-language news writing, while Uzbek more often expands shorthand and clarifies policy or financial terms at first mention. These shifts show how plurilingual mediation works under unequal language prestige: English supplies the first frame, Russian often negotiates through compression, and Uzbek more often negotiates through explicitation. Because the corpus is small, the pattern should be read cautiously.